2006
DOI: 10.1172/jci26223
|View full text |Cite
|
Sign up to set email alerts
|

Decreased vascular lesion formation in mice with inducible endothelial-specific expression of protein kinase Akt

Abstract: To determine whether endothelial Akt could affect vascular lesion formation, mutant mice with a constitutively active Akt transgene, which could be inducibly targeted to the vascular endothelium using the tet-off system (EC-Akt Tg mice), were generated. After withdrawal of doxycycline, EC-Akt Tg mice demonstrated increased endothelial-specific Akt activity and NO production. After blood flow cessation caused by carotid artery ligation, neointimal formation was attenuated in induced EC-Akt Tg mice compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 65 publications
4
70
0
1
Order By: Relevance
“…27,28 This injury is not expected to cause endothelial cell denudation. 27 The integrity of the endothelial cell layer was preserved after FeCl 3 injury in our model as shown by the staining pattern for platelet endothelial cell adhesion molecule-1/CD31, 22 a constitutively expressed endothelial cell adhesion molecule (supplemental Figure 1). Incorporation of ERp57-deficient platelets into the thrombus was substantially decreased ( Figure 2C), with the decrease being statistically significant over the 2-to 10-minute time interval ( Figure 2D).…”
Section: Incorporation Of Erp57-deficient Platelets Into a Growing Thmentioning
confidence: 72%
See 1 more Smart Citation
“…27,28 This injury is not expected to cause endothelial cell denudation. 27 The integrity of the endothelial cell layer was preserved after FeCl 3 injury in our model as shown by the staining pattern for platelet endothelial cell adhesion molecule-1/CD31, 22 a constitutively expressed endothelial cell adhesion molecule (supplemental Figure 1). Incorporation of ERp57-deficient platelets into the thrombus was substantially decreased ( Figure 2C), with the decrease being statistically significant over the 2-to 10-minute time interval ( Figure 2D).…”
Section: Incorporation Of Erp57-deficient Platelets Into a Growing Thmentioning
confidence: 72%
“…The presence of endothelial cells at the site of vascular injury was determined as described elsewhere 22 with some modifications (legend of supplemental Figure 1; see the Blood Web site).…”
Section: Immunostaining Of Endothelial Cellsmentioning
confidence: 99%
“…32 The amount of endothelial injury in the target organ and time course of local NO production after eNOS activation by Akt may play an important role for therapeutic stem cell treatment. 33 In human endothelial cells, the induction of eNOS by TNF-a has recently been described by De Palma et al 34 In contrast, a downregulation of eNOS was observed in association with high levels of TNF-a in patients with type 2 diabetes and microangiopathy. 35 Systemic L-NAME treatment and thereby …”
Section: Discussionmentioning
confidence: 84%
“…Overexpression of Akt1 in endothelial cells in the adult stage also induces pathological blood vessel formation reminiscent of tumor vasculature (Phung et al 2006). However, during blood flow cessation-induced neointimal formation, brief Akt activation in endothelial cells attenuates lesion formation (Mukai et al 2006). Presumably, transient activation of Akt1 in endothelial cells results in the maintenance of a functionally intact endothelial layer, and this pacifies the stimuli that promote smooth muscle growth in this model.…”
Section: Akt Knockout/transgenic Studies (General Information)mentioning
confidence: 86%